Ocena porównawcza kilku metod wyznaczania liczby skupień w zbiorze danych - Korzeniowski, Jerzy (Performance comparison of some methods of determining the number of clusters in a data set, 2006)
This paper is an attempt to compare the performance of an algorithm for determining the number of clusters in a data set proposed by the author with other methods of determining the number o clusters. The other methods include the Rousseeuw silhouette index, the Krzanowski Lai index, the Caliński-Harabasz index and the Hartigan index. The comparison was carried out on the Euclidean space sets generated by the Milligan’s CLUSTGEN program in 4,6 and 8 dimensions. The algorithm proposed does not depend on the grouping of set’s point therefore the other methods were applied to two different in nature grouping methods i.e. the kmeans method and the average linkage agglomeration method. The results seem to prove the new algorithm’s usefulness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 168-174